2011
DOI: 10.1007/s11418-011-0606-y
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of Terminalia bellirica on obesity and metabolic disorders in spontaneously obese type 2 diabetic model mice

Abstract: Visceral obesity induces insulin resistance and is recognized as an important risk factor for metabolic syndrome (MS). Therefore, inhibition of lipid absorption from the intestine is regarded as an effective way of preventing MS. Terminalia bellirica is extensively used in Ayurvedic medicine in India and neighboring countries, and the fruit of this plant has been reported to have hypoglycemic and hypolipidemic effects. In this study, we investigated the preventive effect of a hot water extract of T. bellirica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…33) Considering the gallic acid content of TB, the dose of gallic acid administrated to spontaneously obese type 2 diabetic mice in our previous study is comparable with a dose of 100-300 mg/kg. 24) Therefore, it is reasonable to assume that the gallic acid concentrations (10-30 µM) used here may be consistent with those in mice that were the subject of our previous study. 24) We show here that gallic acid enhanced the expression of the mRNA encoding the marker of adipocyte differentiation Fabp4.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…33) Considering the gallic acid content of TB, the dose of gallic acid administrated to spontaneously obese type 2 diabetic mice in our previous study is comparable with a dose of 100-300 mg/kg. 24) Therefore, it is reasonable to assume that the gallic acid concentrations (10-30 µM) used here may be consistent with those in mice that were the subject of our previous study. 24) We show here that gallic acid enhanced the expression of the mRNA encoding the marker of adipocyte differentiation Fabp4.…”
Section: Discussionsupporting
confidence: 79%
“…In our previous study, we found that TB prevented obesity and various metabolic disorders in spontaneously obese type 2 diabetic mice. 24) In particular, TB prevented the accumulation of visceral fat, improved glucose intolerance, and decreased homeostasis model assessment of insulin resistance (HOMA-IR) in these mice, and we therefore focused on adipocytes as a target of TB. We show here that TB enhanced the differentiation of 3T3-L1 preadipocytes in a similar manner to that of the positive control troglitazone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations